PELATIHAN MENYUSUN ANGGARAN OPERASI BAGI SISWA/I SMA HARAPAN JAYA - Yanti; Kurniawan, Timothy Brian; Darmawan, Alvian Viery (Jurnal Serina Abdimas, 2023)
ABSTRACT Business will prepare a budget before working, because business will benefit greatly from the planning and control that results from the budget that has been made. This PKM partner is SMA Harapan Jaya which is located at Jalan Daan Mogot, Cengkareng-West Jakarta. From the results of discussions with the teacher team at SMA Harapan Jaya, a problem was found where students majoring in social studies received very limited accounting material, while students majoring in science studies did not receive accounting material. Therefore, the PKM Team proposes to provide material provision in the field of accounting on how to prepare an operating budget for a business so that it can be a solution to existing problems. PKM is carried out in three stages: the Preparation Stage, the Implementation Stage, and the Final Stage. The training participants were students of class XII majoring in Science with a total of 13 students of 14 students (92%). The training will be held on Monday, March 6, 2023 onsite. From the quiz results, there were significant differences in results before and after the training was given. Based on the results of the questionnaire, the training participants gave a good general impression of the Training and of the Training Team. This PKM activity has several limitations. First, the students who took part in this training only came from the Science major. Second, the time given is limited so that the material presented is a bit rushed. Suggestions for future training are to provide training on the same topic to students majoring in social studies in two lesson sessions so that the presentation of the material is not rushed Pada umumnya sebuah bisnis akan mempersiapkan anggaran sebelum bekerja, sebab unit bisnis akan mendapatkan manfaat yang besar dari perencanaan dan pengendalian yang dihasilkan dari anggaran yang telah dibuat. Mitra PKM ini adalah SMA Harapan Jaya yang beralamat di Jalan Daan Mogot, Cengkareng-Jakarta Barat. Dari hasil pembicaraan dengan tim guru di SMA Harapan Jaya, ditemukan masalah dimana siswa/i jurusan IPS mendapatkan materi akuntansi yang sangat terbatas, sedangkan siswa/i jurusan IPA tidak mendapatkan materi akuntansi. Oleh sebab itu, Tim PKM mengusulkan untuk memberikan pembekalan materi di bidang akuntansi tentang cara menyusun anggaran operasi suatu bisnis sehingga dapat menjadi solusi atas permasalahan yang ada. PKM dilaksanakan dengan tiga tahap yaitu: Tahap Persiapan, Tahap Pelaksanaan, dan Tahap Akhir. Peserta pelatihan adalah siswa/i kelas XII jurusan IPA dengan jumlah 13 siswa dari total 14 siswa (92%). Pelatihan dilaksanakan pada hari Senin, 06 Maret 2023 secara onsite. Dari hasil kuis, terdapat perbedaan hasil yang signifikan sebelum dan setelah pelatihan diberikan. Berdasarkan hasil kuesioner, peserta pelatihan memberikan kesan umum yang baik terhadap Pelatihan maupun terhadap Tim Pelatih. Kegiatan PKM ini mempunyai beberapa keterbatasan. Pertama, peserta didik yang mengikuti pelatihan ini hanya berasal dari jurusan IPA. Kedua, waktu yang diberikan terbatas sehingga materi yang disampaikan agak terburu-buru. Saran untuk pelatihan mendatang adalah memberikan pelatihan dengan topik yang sama kepada peserta didik jurusan IPS dalam dua sesi pelajaran sehingga pemaparan materi tidak terburu-buru.